Cytoskeletal tension actively sustains the migratory T‐cell synaptic contact. (2nd January 2020) - Kumari, Sudha; Mak, Michael; Poh, Yeh‐Chuin; Tohme, Mira; Watson, Nicki; Melo, Mariane; Janssen, Erin; Dustin, Michael; Geha, Raif; Irvine, Darrell J
Abstract: When migratory T cells encounter antigen‐presenting cells (APCs), they arrest and form radially symmetric, stable intercellular junctions termed immunological synapses which facilitate exchange of crucial biochemical information and are critical for T‐cell immunity. While the cellular processes underlying synapse formation have been well characterized, those that maintain the symmetry, and thereby the stability of the synapse, remain unknown. Here we identify an antigen‐triggered mechanism that actively promotes T‐cell synapse symmetry by generating cytoskeletal tension in the plane of the synapse through focal nucleation of actin via Wiskott–Aldrich syndrome protein (WASP), and contraction of the resultant actin filaments by myosin II. Following T‐cell activation, WASP is degraded, leading to cytoskeletal unraveling and tension decay, which result in synapse breaking. Thus, our study identifies and characterizes a mechanical program within otherwise highly motile T cells that sustains the symmetry and stability of the T cell–APC synaptic contact. Synopsis: When naïve T cells detect cognate antigens on the surface of antigen presenting cells, these highly migratory cells undergo immediate arrest and form radially symmetric cell‐cell conjugate interfaces termed immunological synapses. The stability of such synapses is a crucial determinant of T cell activation, but the T cell‐intrinsic mechanisms that regulate synaptic lifetime are not clear. This study finds that T cells construct specialized actin architectures within the immunological synapse to elevate cytoskeletal tension, thereby reinforcing synaptic stability. In T cells, lamellar protrusions would constantly attempt to break the synapse. Integrin activation is insufficient to sustain the synapse. Antigen recognition‐induced actin foci and associated actomyosin arrangements generate high in‐plane cytoskeletal tension that actively restrains synapse breaking. Via nucleation of actin foci, WASP acts as a central regulator of this mechanism. Downregulation of WASP following T cell activation leads to loss of foci‐dependent actin architecture resulting into synapse unravelling. T cells that lack WASP are predisposed to synapse symmetry breaking, irrespective of the substrate stiffness. Abstract : The stability of contact sites between T‐cells and antigen‐presenting cells—the immunological synapse– is regulated by WASP‐mediated nucleation of F‐actin foci and the actomyosin network, generating cytoskeletal tension that prevents synapse breaking.